(adsbygoogle = window.adsbygoogle || []).push({}); 1. The problem statement, all variables and given/known data

dy/dx = [tex]\frac{[2cos(x)^2-sin(x)^2+y^2]}{[2cos(x)]}[/tex]

Substitute y(x) = sin(x) + [tex]\frac{1}{u(x)}[/tex]

2. Relevant equations

By doing the substitution, it will yield the differential equation for u(x)

du/dx = -u tan(x) - [tex]\frac{1}{2}[/tex]sec(x)

3. The attempt at a solution

I figured out i have to use chain rule. However, if du/dx = du/dy x dy/dx , which dy/dx do i choose? It can be either

this - dy/dx = [tex]\frac{[2cos(x)^2-sin(x)^2+y^2]}{[2cos(x)]}[/tex]

or - y = sin(x) + 1/[u(x)]

dy/dx = cos(x)

Then, I found the dy/du from this equation y = sin(x) + 1/[u(x)] and flipped it around to get du/dy. After multiplying using the chain rule, I dont get the differential equation as shown. Please help me out here. =X

**Physics Forums | Science Articles, Homework Help, Discussion**

Dismiss Notice

Join Physics Forums Today!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# Homework Help: Proving a differential equation using the substitution method

**Physics Forums | Science Articles, Homework Help, Discussion**